Customer satisfaction among university students towards budget hotels. (28th December 2020) - Lim, Kok Oon; Chu, Kai Yuan; Law, Kah Chun; Teo, Boon Keng; Yong, Eng Jun; Chin, Yoon Mei; Foo, Pik-Yin; Loh, Chun T'ing
The budget hotel industry is facing increasing competition from homestay services provided through online platforms such as Airbnb. This paper aims to investigate the influence of customer's personality traits on customer satisfaction in the budget hotel industry in Malaysia. Using the five factor model, this study investigates the relationship between the five variables of openness to experience, conscientiousness, extraversion, agreeableness and neuroticism to customer satisfaction, the dependent variable. Findings show that agreeableness has a positive and significant influence on customer satisfaction for budget hotels. Openness to experience, conscientiousness, extraversion, and neuroticism do not significantly influence customer satisfaction. From the results of the study, budget hotel operators may wish to adopt strategies which focus on the trait of agreeableness to maintain their profitability.